Global Consulting Inc. a study on the collection management practice of an electronic library - Letargo, Ma. Katrina Joy R.; Cruz, Ma. Divina P.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman ix, 51 leaves, 2003)
This study was conducted to determine the effectiveness of the existing content management practice of the Government Consulting Inc. (GCI) Library. The library is a storage of key government information relevant to the GCI organization. To measure this effectiveness, the different components of an effective Collection Management (CM) Program were analyzed. The descriptive method of inquiry was carried out for this study.
Findings show that despite the existence of the CM Program components, their collection management practices are constantly changing. They are stakeholder dependent and the process involved in updating the information must be streamlined from assessment to preservation. It was therefore recommended that the preservation process must be reviewed and streamlined. Another recommendation is to come up with a process of utilizing the user's feedback, results of which must be factored in the improvement of the collection management activities.
This study can serve as a guide for collection management librarians in organizing information resources online, synthesizing digital resources and coordinating electronic access and delivery options to users in a distributive manner.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Collection management (Libraries) -- Philippines -- Manila; Digital libraries -- Philippines -- Manila; Electronic information resources -- Philippines -- Manila